Analisa Korelasi Return Indeks â Indeks Saham terhadap Indeks Harga Saham Gabungan pada Bursa Efek Indonesia - Mulyono, Mulyono (Binus Business Review, 2015)
Stock market generally has the stock price index that measures the performance of stock trading, the Indonesia Stock Exchange has a stock price index that is widely known as Jakarta Composite Index (IHSG). During its development, the Indonesia Stock Exchange has many alternative indexes that measure the performance of stock trading. Research that is to be conducted on the correlation between return of the stock index listed in Indonesia Stock Exchange and return of Jakarta Composite Index. Return stock index listed on the Indonesia Stock Exchange, namely, LQ45 Index, Jakarta Islamic Index (JII), KOMPAS100 Index, BISNIS-27 Index, PEFINDO25 Index and SRI-KEHATI Index, has a close relationship with the return Jakarta Composite,Index which is a reflection of the movement of all existing stock in the market. Return of stocks index that have the highest coefficient correlation is KOMPAS100 In dex, which have return index coefficient correlation is 0.949, thus KOMPAS100 Index that consisting of 100 stocks, based on the results of the study can be used as an alternative investment to get a return that is at least equal or close to the yield given by Jakarta Composite Index(IHSG) that consists of 445 stocks